CRITICISM OF LITERATURISM IN THE 1990S: FOCUSING ON MUNHAKDONGNE - YANG, Soonmo (International Journal of Korean Humanities and Social Sciences, 2021)
Regarding the recent critical evaluations surrounding the Korean literature field in the 1990s, this paper argues that the criticism should be presented at a more ‘intrinsic’ and ‘reflective’ level. In particular, through 문학동네 Munhakdongne (the Literature Village) as a negative origin of today, I would like to examine the rationality of ‘literaturism’ (the art for art’s sake principle) in the 90s, which is difficult to criticize easily. This ‘rationality’ is not only one that is repeated and persuasive in today’s literature, but also one that shares much from the perspective of critically judging Munhakdongne. By critically examining the nature of this ‘rationality’ in the 1990s, this paper aims to define today’s Korean literature field and to prepare for the possibility of moving beyond it.